2014
DOI: 10.1371/journal.pone.0096888
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Potential Effectiveness of Dignity Therapy for People with Motor Neurone Disease

Abstract: BackgroundMotor neurone disease (MND) practice guidelines suggest developing interventions that will promote hope, meaning, and dignity to alleviate psychological distress, but very little research has been done. This study begins to address this need by exploring the use of dignity therapy with people with MND. Dignity therapy is a brief psychotherapy that promotes hope, meaning and dignity, and enhances the end of life for people with advanced cancer. The aims of this study are to assess the feasibility, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 42 publications
2
65
0
1
Order By: Relevance
“…The Patient Dignity Inventory was the most common tool used in the included articles (Table 5). It was used in ten studies (Abbaszadeh, Borhani, & Rabori, 2015; Bentley, O'Connor, Kane, & Breen, 2014; Borhani, Abbaszadeh, & Moosavi, 2014; Chochinov et al, 2016; Hall, Goddard, Martin, Opio, & Speck, 2013; Li, Wang, & Ho, 2018; Oechsle, Wais, Vehling, Bokemeyer, & Mehnert, 2014; Rullán et al, 2015; Sautier, Vehling, & Mehnert, 2014; Vehling & Mehnert, 2014) and translated into and validated in nine languages (Persian, German, Greek, Czech, Italian, Finnish, Hungarian, Spanish and Mandarin). The Caring Behaviors Inventory (CBI) was outlined in four papers (Aupia et al, 2018; He et al, 2013; Papastavrou et al, 2012a; Papastavrou et al, 2012b) (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…The Patient Dignity Inventory was the most common tool used in the included articles (Table 5). It was used in ten studies (Abbaszadeh, Borhani, & Rabori, 2015; Bentley, O'Connor, Kane, & Breen, 2014; Borhani, Abbaszadeh, & Moosavi, 2014; Chochinov et al, 2016; Hall, Goddard, Martin, Opio, & Speck, 2013; Li, Wang, & Ho, 2018; Oechsle, Wais, Vehling, Bokemeyer, & Mehnert, 2014; Rullán et al, 2015; Sautier, Vehling, & Mehnert, 2014; Vehling & Mehnert, 2014) and translated into and validated in nine languages (Persian, German, Greek, Czech, Italian, Finnish, Hungarian, Spanish and Mandarin). The Caring Behaviors Inventory (CBI) was outlined in four papers (Aupia et al, 2018; He et al, 2013; Papastavrou et al, 2012a; Papastavrou et al, 2012b) (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…One study examined the feasibility of DT for people with motor neurone disease (MND) (Bentley, O'Connor, Kane, & Breen, ). This study conducted DT with 29 individuals diagnosed with MND in Australia.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have addressed pragmatic aspects of delivering DT, including time taken, costs expended, and length of documents, but the findings are limited by incomplete information reported in these studies (Hall et al, ; Johns, ; Montross et al, ). Two studies noted that the time required to edit documents may be excessive and problematic for clinical implementation (Hall et al, ; Passik et al, ), one noted that travel time, cancelled appointments, and delays were common issues that compounded the substantial time commitment required by clinicians (Hall et al, ), and another indicated that some physical symptoms increase the time required to complete the therapy (Bentley, O'Connor, Kane, et al, ). All studies thus far indicate that DT is substantially more time consuming to deliver than indicated in Chochinov's training materials, which states the intervention can be completed in 5–6 hr of therapist time (Chochinov, ; Chochinov & McKeen, ).…”
Section: Discussionmentioning
confidence: 99%
“…This instrument can be used as a screening method, not only in clinical practice, but also in research, which focuses on understanding the problems influencing patient dignity in the early and late stages of cancer, 15e19 in terminal stages of noncancer illnesses, and in severe geriatric frailty. 3,20,21…”
Section: Methodsmentioning
confidence: 99%